Effects of manufacturing methods of abalone gel as a desensitisation material on the closing of dentinal tubules - Sri Budi Barunawati; Wayan Tunas Artama; Suparyono Saleh; Siti Sunarintyas; Yosi Bayu Murti (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2020)
Background: Abalone (Haliotis varia Linnaeus) shells possess a high arginine content and are expected to be an alternative desensitisation material that is both insoluble and able to properly close dentinal tubules. Different methods of manufacturing abalone gel affect the molecular weight, hydrophilic or hydrophobic properties and protein content of the lysis. Purpose: This study aimed to determine the effects of different manufacturing methods on the dentinal tubule closure of abalone desensitisation gel. Methods: This study involved the extraction of abalone shells followed by preparative and thin-layer chromatography. The drying of the samples was carried out by the precipitation, drying, and addition methods. The research was divided into eight treatment groups, each consisting of three samples (F1, F2, F3). Each sample was applied to two study subjects’ post-extracted third molars, which were cut into disc shapes and subsequently etched with 6% citric acid. The percentage of dentinal tubule occlusion was calculated by Image J (NIH, USA) software. Data were analysed using three-way ANOVA. Results: The results showed that there were significant differences (p < 0.05) both in terms of the effects of the samples with deposition and addition on the occlusion of the dentinal tubules and in terms of the interactions between the samples with drying and addition. There was no significant difference (p > 0.05) in terms of the interactions of the samples’ three manufacturing methods. Conclusion: The manufacture of abalone gel as a desensitisation material requires a minimum of two interactions between the sample-making method and the addition, deposition, and drying methods. The best method was deposition.